Impact of upstream watershed intervention on downstream irrigation, productivity and livelihoods of farming communities - CGIAR Research Program on Water, Land and Ecosystems (2021)
The community-based watershed management approach provides an example of contextualized knowledge and locally specific approaches that were successfully applied to transforming a degraded and unproductive landscape. Watershed interventions have reduced peak flows and resulted in a regulated flow and increased baseflow over the post rainy seasons. The sediment concentration reduced from high peaks (100-130 g/l) in 2018 to 20-25 g/l afterward. This change resulted in increased water yield to expanding irrigation areas and recharge springs to use for production intensification.